Cultureel jaarboek 1999 : 53e jaargang - Provincie Oost-Vlaanderen (Gent : Provincieraad van Oost-Vlaanderen, 2001)
Joliet, Ilse ; Tahon, Johan ; Blancquaert, Lieve ; Boon, Elke ; Daels, Luc ; Vandekerckhove, Hans ; Vekemans, Bruno ; Claus, Hugo ; Gentils, Paul ; Greenaway, Peter ; Huycke, David ; De Smet, Gery ; Tasseel, Nadine ; Van Nazareth, Herman ; Steel, Georges ; Vervaet, Bert ; Woedstad, Gaston ; Servais, Raoul
boek